Cultural flows in high-end cuisine from the periphery to the center - Lane, Christel; Opazo, M. Pilar (Routledge, 2024)
Focusing on high-end cuisine, this book examines the flows of culinary knowledge from culturally peripheral locations to two cities at the global center, London and New York. Through the voices of chefs and other professionals in the industry, this book invites readers to rethink our understandings of high-end and ethnic cuisines, as well as the conventions and principles that shape the contemporary field of gastronomy and fine-dining. It examines a broad range of cuisines, including Peruvian, Korean, Mexican, Malaysian, Senegalese, West African, Thai, Chinese, and Indian, and conveys the chefs' voices as they strive to elevate their cuisines through discursive and material means, including the shaping of menus, and restaurant decor. While the main focus falls on chefs as the producers of high-end cuisines, this book also gives consideration to their consumers, that is cosmopolitan diners in the two global cities, and to the influence of culinary intermediaries judging and legitimizing their high-end status. Theoretically, this book contributes to the debate on cultural globalization. It undertakes a study of hitherto rarely examined cultural counterflows or reverse cultural globalization and analyzes both the precipitants of this occurrence and the effects of cultural counterflows on both Western global cities and the home countries of chefs. This book will be of great interest to students and scholars of food studies, food cultures, cultural globalization, and culinary studies.
Keywords: Restaurants -- Influence -- Case studies.; Cultural relations -- Case studies.; Cultural fusion -- Case studies.; Cooking -- Political aspects -- Case studies.; Restaurants -- England -- London -- Evaluation.; Restaurants -- New York (State) -- New York -- Evaluation.; elektronické knihy; electronic books